The type of Cypella Herbertii subsp. brevicristata Ravenna (Iridaceae: Tigridieae) - Deble, Leonardo Paz; Alves, Fabiano da Silva (Balduinia, 2017)
In the absence of original vouchers deposited in Herbaria of Cypella Herbertii subsp. brevicristata a neotype is proposed, having as base collections performed in the typical region of occurrence, in Artigas Department, Uruguay. Furthermore, description, photos, geographic distribution, conservation data are supplied, as well as its taxonomic relationships are discussed.